Comparative Preclinical Evaluation of Nelumbo Nucifera and Related Herbal Extracts in Breast Cancer Models: Molecular Pathways and Effectiveness - Khairani Fitri; Marwan Saad Azzubaidi; Nurul Huda Mat Hassan (Newinera Publisher, 2025)
This study provides a comparative preclinical evaluation of Nelumbo nucifera (lotus) and related herbal extracts in breast cancer models, focusing on their targeted molecular pathways and effectiveness. The analysis includes both in vitro and in vivo studies involving lotus leaf, seedpod, and related plant extracts from Nymphaea, Moringa, and Taraxacum. The findings demonstrate that N. nucifera leaf alcoholic extract exhibits the most comprehensive anticancer profile, with effects validated in multiple models, including those of ER-negative and radioresistant cells. The lotus seedpod extracts also demonstrated promising activity against resistant tumors by inhibiting DNA repair. Other herbal candidates demonstrated apoptotic or cytotoxic effects but were limited in scope or lacked in vivo confirmation. These results support the further development of lotus-derived compounds as promising multi-pathway therapeutic agents for breast cancer.